Habitat modification in tidepools by bioeroding sea urchins and implications for fine‐scale community structure. (11th February 2014) - Davidson, Timothy M.; Grupe, Benjamin M.
Abstract By creating novel habitats, habitat‐modifying species can alter patterns of diversity and abundance in marine communities. Many sea urchins are important habitat modifiers in tropical and temperate systems. By eroding rocky substrata, urchins can create a mosaic of urchin‐sized cavities or pits separated by exposed, often flat surfaces. These microhabitats appear to harbor distinct assemblages of species. We investigated how a temperate rocky intertidal community uses three small‐scale (<100 cm2) microhabitats created by or adjacent to populations of the purple sea urchin (Strongylocentrotus purpuratus): pits occupied by urchins, unoccupied pits, and adjacent flat spaces. In tidepools, flat spaces harbored the highest percent cover of algae and sessile fauna, followed by empty pits and then occupied pits. The Shannon diversity and richness of these sessile taxa were significantly higher in flat spaces and empty pits than in occupied pits. The composition of these primary space holders in the microhabitats also varied. Unlike primary space holders, mobile fauna exhibited higher diversity and richness in empty pits than in flat spaces and occupied pits, although results were not significant. The protective empty pit microhabitat harbored the highest densities of most trophic functional groups. Herbivores, however, were densest in flat spaces, concordant with high algal coverage. These results suggest the habitats created by S. purpuratus in addition to its biological activities alter community structure at spatial scales finer than those typically considered for sea urchins.